2003
DOI: 10.1007/s15010-003-3159-5
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniae Carriage and Infection in Hospitalized Children with Respiratory Tract Diseases

Abstract: Background:The importance of Chlamydia pneumoniae respiratory tract infection in childhood is under discussion. Patients and Methods: 798 hospitalized children with respiratory tract diseases were prospectively studied during a 2-year period by polymerase chain reaction and enzyme immunoassay (PCR-EIA) detection from throat swabs. Paired serum samples were used to screen for Chlamydia antibodies. Results: C. pneumoniae was detected by PCR-EIA in 74 children. Prevalence was 11% in lower and 4% in upper respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 22 publications
2
9
1
Order By: Relevance
“…pneumoniae infections, the 6.0% rate in children with ARTIs found in the present study is similar to the 6.7% (4/112) found in a study performed by Kurz et al [20] in Vienna, Austria, and lower than the 9.3% reported by Schmidt et al [21] for Greifswald, Germany. No seasonality or correlation with climatic conditions was found in our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…pneumoniae infections, the 6.0% rate in children with ARTIs found in the present study is similar to the 6.7% (4/112) found in a study performed by Kurz et al [20] in Vienna, Austria, and lower than the 9.3% reported by Schmidt et al [21] for Greifswald, Germany. No seasonality or correlation with climatic conditions was found in our study.…”
Section: Discussionsupporting
confidence: 90%
“…pneumoniae and C . pneumoniae infections are most common in school-aged children, followed by children from 1 to 5 years old, but rare in infants [16,21-24]. In contrast, we found that M .…”
Section: Discussionmentioning
confidence: 67%
“…If there is an influence on the disease, one would expect no seasonal variation in prevalence, since RCBP can be diagnosed across the whole year. In asymptomatic children and those with acute respiratory tract diseases, higher C. pneumoniae prevalence has been found between November and February, as well as in April [23,24]. In the population we studied, however, no seasonal variation in prevalence could be detected.…”
Section: Discussionmentioning
confidence: 61%
“…In the elderly it often exceeds 80 % [13]. This is not the consequence of a lower prevalence of C. pneumoniae infections in younger children, as there was no age-dependency in prevalence by using PCR-EIA in children with acute respiratory tract diseases [23] or kindergarten and school children [24]. To study the effect of C. pneumoniae infection on respiratory tract disease in children with RCBP, PCR-EIA has to be used, therefore.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation